Effect of integrated nutrient management on growth, yield, nutritional value, and nutraceutical quality of onion bulbs (Allium cepa L.): Effects of nutrient supply sources on onion bulb yield and quality - Bhardwaj, Raju Lal; Sharma, Anita; Meena, Premlata; Choudhary, K; Kumawat, S R; Parashar, Aabha (Journal of Spices and Aromatic Crops, 2025)
The use of mineral fertilizers for onion cultivation can degrade soil physical properties and microbial diversity, thereby adversely affecting crop productivity and nutritional quality of onion bulbs. To address this concern, a long-term field experiment was conducted with six treatments to evaluate the effects of varying proportions of mineral fertilizers and organic manures, combined with the plant growth-promoting microorganisms (PGPMs), on bulb yield attributes, nutritional quality, sensory characteristics, spicing superiority, and nutraceutical contents of onion bulbs.​ The results demonstrated that applying 100 per cent of the recommended dose of fertilizers (RDF) through organic manures, in combination with PGPMs inoculation, significantly improved plant growth parameters (ranging from 2.39% to 21.95%), bulb yield attributes (3.28% to 16.53%), physicochemical properties (7.30% to 53.08%), economic returns (7.64% to 18.69%), total mineral content (0.68% to 39.88%), and nutraceutical concentrations (21.47% to 75.32%). Moreover, this integrated approach enhanced crop resistance mechanisms against major diseases and insect infestations compared to the exclusive use of 100% RDF via mineral fertilizers.​ Overall, the study suggests that integrating organic manure-based RDF with PGPMs inoculation enhances onion productivity and nutritional quality. In conclusion, the combined use of organic manure and PGPMs significantly improved the nutritional density, organoleptic properties, and flavour qualities of onion bulbs, while also contributing to reduction of pathogen and insect pest infestations during cultivation.